Canagliflozin alleviates high glucose-induced peritoneal fibrosis via HIF-1α inhibition - Wang, Jian; Lv, Xin; A-Ni-Wan, A-Shan-Jiang; Tian, Sha-Sha; Wang, Jun-Mei; Liu, Hong-Yan; Fan, Xiao-Guang; Zhou, Sai-Jun; Yu, Pei (Frontiers in Pharmacology, 2023)
The cardioprotective effects of sodium-glucose cotransporter type 2 (SGLT2) inhibitors have been demonstrated in many studies. However, their benefits for end-stage kidney disease patients, particularly those on peritoneal dialysis, remain unclear. SGLT2 inhibition has shown peritoneal protective effects in some studies, but the mechanisms are still unknown. Herein, we investigated the peritoneal protective mechanisms of Canagliflozin in vitro by simulating hypoxia with CoCl2 in human peritoneal mesothelial cells (HPMCs) and rats by intraperitoneal injection of 4.25% peritoneal dialysate simulating chronic high glucose exposure. CoCl2 hypoxic intervention significantly increased Hif-1α abundance in HPMCs, activated TGF-β/p-Smad3 signaling, and promoted the production of fibrotic proteins (Fibronectin, COL1A2, and α-SMA). Meanwhile, Canagliflozin significantly improved the hypoxia of HPMCs, decreased Hif-1α abundance, inhibited TGF-β/p-Smad3 signaling, and decreased the expression of fibrotic proteins. Five-week intraperitoneal injection of 4.25% peritoneal dialysate remarkably increased peritoneal Hif-1α/TGF-β/p-Smad3 signaling and promoted peritoneal fibrosis and peritoneal thickening. At the same time, Canagliflozin significantly inhibited the Hif-1α/TGF-β/p-Smad3 signaling, prevented peritoneal fibrosis and peritoneal thickening, and improved peritoneal transportation and ultrafiltration. High glucose peritoneal dialysate increased the expression of peritoneal GLUT1, GLUT3 and SGLT2, all of which were inhibited by Canagliflozin. In conclusion, we showed that Canagliflozin could improve peritoneal fibrosis and function by ameliorating peritoneal hypoxia and inhibiting the Hif-1α/TGF-β/p-Smad3 signaling pathway, providing theoretical support for the clinical use of SGLT2 inhibitors in patients on peritoneal dialysis.